Old world Italian : recipes & secrets from our travels in Italy - Thorisson, Mimi (Clarkson Potter, 2020)
Mimi explores the beautiful coasts and countrysides of Italy in this lavishly photographed cookbook featuring simple, authentic recipes inspired by the country's devoted producers and rich food heritage. Beloved for her gorgeous cookbooks A Kitchen in France and French Country Cooking, Mimi Thorisson, along with her lively family and smooth fox terriers in tow, immersed readers in the warmth of their convivial lives in rural France. In their newest cookbook, the Thorissons pause their lives in the idyllic French countryside to start a new adventure in Italy and satisfy their endless curiosity and passion for the magic of Italian cooking. Old World Italian captures their journey and the culinary treasures they discovered. From Tuscany to Umbria to Naples and more, Mimi dives into Italy's diverse regional cuisines and shares 100 recipes for authentic, classic dishes, enriched by conversations with devoted local food experts who share their timeworn techniques and stories. You'll indulge in dishes culled from across the country, such as plump agnolotti bathed in sage and butter from the north, the tomato-rich ragus and pastas of the southwest, and the multifaceted, seafood-laden cuisine of Sicily. The mysteries of Italian food culture will unravel as you learn to execute a perfect Neapolitan-style pizza at home or make the most sublime yet elemental cacio e pepe. Full of local color, history, and culture, plus evocative, sumptuous photography shot by Mimi's husband, Oddur Thorisson, Old World Italian transports you to a seat at the family's table in Italy, where you may never want to leave.